Project management in CLDS: The methodologies of the quality management plan in social services: https://doi.org/10.53809/TS_ISS_2023_n.4_174-189 ("Temas Sociais" Journal, 2023)
The quality management plan is an important area of knowledge applied to project management, which accompanies the entire life cycle of the project. In this sense, and as part of the results of the author's master's thesis, the purpose was to analyse and understand the quality management plans used in CLDS programs. To study this topic, qualitative research was used, with 24 participants, based on the case study methodology and the semi-structured interview as a data collection instrument. The results of this research highlight the valorisation of quality assessment metrics as mechanisms for continuous improvement.